Augustine's Conversion : A Guide to the Argument of Confessions I-IX - Starnes, Colin (Book collections on Project MUSE., 2006)
Colin Starnes teaches Patristics in the Classics Department at Dalhousie University in Halifax. In addition to publishing numerous articles on the transition from antiquity to the medieval period, he is the author of The New Republic: A Commentary on Book I of More's Utopia Showing Its Relation to Plato's Republic (WLU Press, 1990).